2016
DOI: 10.1038/aps.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Tubeimoside-1 induces oxidative stress-mediated apoptosis and G0/G1 phase arrest in human prostate carcinoma cells in vitro

Abstract: Aim: Tubeimoside-1 (TBMS1), a triterpenoid saponin extracted from the Chinese herbal medicine Bolbostemma paniculatum (Maxim) Franquet (Cucurbitaceae), has shown anticancer activities in various cancer cell lines. The aim of this study was to investigate the anticancer activity and molecular targets of TBMS1 in human prostate cancer cells in vitro. Methods: DU145 and P3 human prostate cancer cells were treated with TBMS1. Cell viability and apoptosis were detected. ROS generation, mitochondrial membrane potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…In recent decades, the primary pharmacological findings of TBMS I were to demonstrate its potent anti-cancer activity (Chen et al, 2012(Chen et al, , 2016Gu et al, 2016;Lin et al, 2014Lin et al, , 2016Yang et al, 2016). In this study, we demonstrated, for the first time, that TBMS I could effectively prevent arthritis progression and decrease severity of FLSs play a critical role in RA pathogenesis by producing cytokines that perpetuate inflammation and proteases that contribute to cartilage destruction.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In recent decades, the primary pharmacological findings of TBMS I were to demonstrate its potent anti-cancer activity (Chen et al, 2012(Chen et al, , 2016Gu et al, 2016;Lin et al, 2014Lin et al, , 2016Yang et al, 2016). In this study, we demonstrated, for the first time, that TBMS I could effectively prevent arthritis progression and decrease severity of FLSs play a critical role in RA pathogenesis by producing cytokines that perpetuate inflammation and proteases that contribute to cartilage destruction.…”
Section: Discussionmentioning
confidence: 49%
“…Franquet (Cucurbitaceae), has been demonstrated to possess antiviral, anti‐inflammatory and antivenom effects (Wu et al, ; Yu, Ma, & Jiang, ; Yu, Ma, & Yu, ). In addition, a growing body of evidence indicates that TBMS I has significant antitumor effects, such as inhibiting the cell proliferation, arresting the cell cycle and promoting the cell apoptosis (Chen et al, ; Gu et al, ; Lin et al, , ; Yang et al, ). Given the known antitumor effects of TBMS I and the similar features observed between cancer cells and activated FLS, we hypothesized that TBMS I may exert a therapeutic effect on RA through attenuating the destructive phenotypes of activated FLS.…”
Section: Introductionmentioning
confidence: 99%
“…Itraconazole treatment initially caused a proliferative burst, forcing dormant cells to cycle briefly and subsequently enter irreversible G1 cell cycle arrest and senescence [31,48]. Furthermore, tubeimoside-1 potently suppressed the growth of human prostate cancer cells via inducing oxidative stress-mediated apoptosis and G0/G1 phase arrest [49]. Arctigenin, the active component of burdock root, enhanced p27 Kip1 protein levels through inhibition of Akt and stimulation of FOXO3a activity, in turn, suppressing CDK2 kinase activity and finally inducing overall inhibition of HSC proliferation and G0/G1 phase arrest [50].…”
Section: Other Pathwaysmentioning
confidence: 99%
“…Tubeimoside-1 inhibited the growth of several cancer cells including gliomas, lung cancer and liver cancer (Zhang et al, 2011; Wang et al, 2011a; Jia et al, 2015). Tubeimoside-1 induced phosphorylation of apoptosis signal-regulating kinase 1 (ASK-1) and its downstream target proteins JNK and p38 in a dose-dependent manner, leading to mitochondrial apoptosis in DU145 human prostate cancer cells (Yang et al, 2016). Activation of MAPK-JNK signaling pathway plays an important role in tubeimoside-1 induced cell cycle arrest in lung cancer cells (Hao et al, 2015).…”
Section: Components Isolated From Tcms That Inhibit Mapkmentioning
confidence: 99%